Design objective tests using the computer program in developing the Arabic language for non-native speakers - Moh. Ismail (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2019)
AbstractThe primary purpose of a language test is to provide a measure that we can interpret as an indicator of an individual's language ability. The most important consideration in designing and developing a language test is the use for which it is intended so that the most important quality of a language test is its usefulness. And the essential measurement qualities are reliability and construct validity. Reliability is often defined as the consistency of measurement.A reliable test score will be consistent across different characteristics of the testing situation. And the construct validity pertains to the meaningfulness and appropriateness of the interpretations that we make based on test scores. Computer scoring has the advantage of providing instant results and this feature can be exploited to create individualized assessments. Computers have been used for managing item banks, scoring multiple-choice responses, generating score reports, conducting statistical analysis, and storing test-takers records.These roles will continue to contribute to the efficiency of language testing. Computer-based assessments are generally conservative and tend to reflect what was already possible in paper-based (or face to face) assessment. The concern in computer-assisted testing appears to pose a question of whether or computer-assisted language testing is valid. Validity refers to the degree to which inference from and uses of test scores can be justified. Whenever language instruction is offered online, it makes sense for teachers to at least consider online assessment as well. The most efficient option for doing so is course management software that allows the teacher to construct language tests based on computer programs Keywords : Language Assessment, Computer-assisted Language Testing (CALT), Arabic Language for Non, E-Learning,